2018
DOI: 10.3168/jds.2018-14675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitosan and whole raw soybeans on ruminal fermentation and bacterial populations, and milk fatty acid profile in dairy cows

Abstract: The objective of this study was to evaluate whether providing chitosan (CHI) to cows fed diets supplemented with whole raw soybeans (WRS) would affect the nutrient intake and digestibility, ruminal fermentation and bacterial populations, microbial protein synthesis, N utilization, blood metabolites, and milk yield and composition of dairy cows. Twenty-four multiparous Holstein cows (141 ± 37.1 d in milk, 38.8 ± 6.42 kg/d of milk yield; mean ± SD) were enrolled to a 4 × 4 Latin square design experiment with 23-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
44
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 69 publications
11
44
4
2
Order By: Relevance
“…The present study also found that a similar decrease in CH 4 synthesis without an adverse effect on diet digestion could be accomplished by reducing chitosan solubility (88.00% deacetylated). This agrees with previous reports which indicated no adverse effect of chitosan on nutrient digestibility when little roughage was used in vivo [22,23] or in vitro [9]. Moreover, Haryati et al [8] noted that CH 4 production decreased when chitosan was added at 2% of substrate.…”
Section: In Vitro Rumen Parameters and Ch 4 Concentrationsupporting
confidence: 91%
See 4 more Smart Citations
“…The present study also found that a similar decrease in CH 4 synthesis without an adverse effect on diet digestion could be accomplished by reducing chitosan solubility (88.00% deacetylated). This agrees with previous reports which indicated no adverse effect of chitosan on nutrient digestibility when little roughage was used in vivo [22,23] or in vitro [9]. Moreover, Haryati et al [8] noted that CH 4 production decreased when chitosan was added at 2% of substrate.…”
Section: In Vitro Rumen Parameters and Ch 4 Concentrationsupporting
confidence: 91%
“…This could be due to properties such as chitosan's high degree of deacetylation, which may modify methanogen's cell wall permeability, thus reducing CH 4 production [8]. In addition, positively charged chitosan may interfere with negatively charged methanogens and cause a leakage of protein and other intracellular compositions from the cytosol [9]. An additional theory related to chitosan is that of agglutination.…”
Section: In Vitro Rumen Parameters and Ch 4 Concentrationmentioning
confidence: 99%
See 3 more Smart Citations